Reduction of atmospheric fine particle level by restricting the idling vehicles around a sensitive area. (3rd July 2018) - Lee, Yen-Yi; Lin, Sheng-Lun; Yuan, Chung-Shin; Lin, Ming-Yeng; Chen, Kang-Shin
ABSTRACT: Atmospheric particles are a major problem that could lead to harmful effects on human health, especially in densely populated urban areas. Chiayi is a typical city with very high population and traffic density, as well as being located at the downwind side of several pollution sources. Multiple contributors for PM2.5 (particulate matter with an aerodynamic diameter ≥2.5 μm) and ultrafine particles cause complicated air quality problems. This study focused on the inhibition of local emission sources by restricting the idling vehicles around a school area and evaluating the changes in surrounding atmospheric PM conditions. Two stationary sites were monitored, including a background site on the upwind side of the school and a campus site inside the school, to monitor the exposure level, before and after the idling prohibition. In the base condition, the PM2.5 mass concentrations were found to increase 15% from the background, whereas the nitrate (NO3 − ) content had a significant increase at the campus site. The anthropogenic metal contents in PM2.5 were higher at the campus site than the background site. Mobile emissions were found to be the most likely contributor to the school hot spot area by chemical mass balance modeling (CMB8.2). On the other hand, the PM2.5 in the school campus fell to only 2% after idling vehicle control, when the mobile source contribution reduced from 42.8% to 36.7%. The mobile monitoring also showed significant reductions in atmospheric PM2.5, PM0.1, polycyclic aromatic hydrocarbons (PAHs), and black carbon (BC) levels by 16.5%, 33.3%, 48.0%, and 11.5%, respectively. Consequently, the restriction of local idling emission was proven to significantly reduce PM and harmful pollutants in the hot spots around the school environment. Implications : The emission of idling vehicles strongly affects the levels of particles and relative pollutants in near-ground air around a school area. The PM2.5 mass concentration at a campus site increased from the background site by 15%, whereas NO3 − and anthropogenic metals also significantly increased. Meanwhile, the PM2.5 contribution from mobile source in the campus increased 6.6% from the upwind site. An idling prohibition took place and showed impressive results. Reductions of PM2.5, ionic component, and non-natural metal contents were found after the idling prohibition. The mobile monitoring also pointed out a significant improvement with the spatial analysis of PM2.5, PM0.1, PAH, and black carbon concentrations. These findings are very useful to effectively improve the local air quality of a densely city during the rush hour.